HUBUNGAN STATUS SOSIAL EKONOMI DENGAN PERILAKU IBU DALAM PENCARIAN PELAYANAN KESEHATAN BALITA DENGAN INFEKSI SALURAN PERNAPASAN AKUT Penelitian Pasca Gem - , Yulinar Wusanani; , Prof. dr. Djauhar Ismail, MPH, Ph.D, Sp.AK ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. Delay in health seeking behavior is one of the causes of high mortality in children due to acute respiratory infection (ARI). Factors that may affect health care seeking behavior are socioeconomic status, maternal age, maternal education, parentsâ perception, childâs age, the number of children under five in the family, and natural disaster. Objective. To figure out the relationship between socio economic status and motherâs healthcare seeking behavior for children under five with ARI. Method. This is a cross sectional study using secondary data obtained from a survey of Child Health Need Assessment (CHNA). The data was collected by interviewing parents or guardian of children under five using structured questionnaire. To value variables affecting the health seeking behavior for children under five with ARI analysis of logistic regression was used. Results. Of the 665 infants enrolled in this study, there were 442 (66,5%) infants with ARI. Health care seeking behavior in the majority (81,7%) mothers was good. The result of this study show that socioeconomic status did not affect the health care seeking behavior for children under five with ARI (OR 1.33